2023
DOI: 10.4055/cios22128
|View full text |Cite
|
Sign up to set email alerts
|

Is Ultrasound (US)-Guided Platelet-Rich Plasma Injection More Efficacious as a Treatment Modality for Lateral Elbow Tendinopathy Than US-Guided Steroid Injection?: A Prospective Triple-Blinded Study with Midterm Follow-up

Abstract: Background Lateral elbow tendinopathy (LET) has an array of modalities described for its management. The present study analyzed two modalities used for managing the condition. Methods The present study included 64 non-athletes with LET who failed conservative treatment that included avoiding strenuous activities, ice-fomentation, non-steroidal anti-inflammatory drugs, bracing, and physiotherapy for 6 months. A random allocation of the participants was done, with one gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…Discussion: In the studies by Gautam et Al, (2015), Cai et Al, ( 2019) and Kamble et Al, (2022) USguided application was used, demonstrating more positive results compared to the study by Keene et Al, (2019), which used the application guided by the doctor's palpation. Regarding the preparation method, the double centrifugation demonstrated in the studies by Cai et Al, (2019) and Kamble et Al, (2022), was also associated with greater benefits compared to a single centrifugation in the study by Keene et Al, (2019). Conclusion: Most studies have demonstrated the effectiveness of using PRP in the regeneration of tendinopathies.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Discussion: In the studies by Gautam et Al, (2015), Cai et Al, ( 2019) and Kamble et Al, (2022) USguided application was used, demonstrating more positive results compared to the study by Keene et Al, (2019), which used the application guided by the doctor's palpation. Regarding the preparation method, the double centrifugation demonstrated in the studies by Cai et Al, (2019) and Kamble et Al, (2022), was also associated with greater benefits compared to a single centrifugation in the study by Keene et Al, (2019). Conclusion: Most studies have demonstrated the effectiveness of using PRP in the regeneration of tendinopathies.…”
mentioning
confidence: 86%
“…Methodology: To carry out this study, a systematic review of the literature was carried out, using as a basis the Preferred Reporting Items for Systematic review and Meta-Analysis, and adopting the following descriptors from the Medical Subject Headings, in English: platelet-rich plasma (plasma rich in platelets), physiotherapy, tendinopathy and tendon injury, in the Pubmed electronic database. Results: In this study, 4 articles were selected, 3 of which showed significant efficacy in improving function and pain in the injured limb after the application of PRP (GAUTAM, et al, 2015;CAI, et al, 2019;KAMBLE, et al, 2022), however, the study by Keene et al, (2019), did not detect a significant improvement with the use of PRP in relation to placebo, considering that the application of PRP in this study was guided only by the doctor's palpation. Discussion: In the studies by Gautam et Al, (2015), Cai et Al, ( 2019) and Kamble et Al, (2022) USguided application was used, demonstrating more positive results compared to the study by Keene et Al, (2019), which used the application guided by the doctor's palpation.…”
mentioning
confidence: 95%
“…Metodologia: Para a realização deste estudo foi feita uma revisão sistemática da literatura, utilizando como base o Preferred Reporting Items for Systematic review and Meta-Analysis, e adotando os seguintes descritores da Medical Subject Headings, em língua inglesa: platelet-rich plasma (plasma rico em plaquetas), physiotherapy (fisioterapia), tendinopathy (tendinopatia) e tendon injury (lesões no tendão), na base de dados eletrônica Pubmed. Resultados: Neste estudo foram selecionados 4 artigos, os quais 3 apresentaram eficácia significativa na melhora da função e do quadro álgico no membro lesionado após a aplicação de PRP(GAUTAM, et al, 2015; CAI, et al, 2019;KAMBLE, et al, 2022), contudo, o estudo deKeene et al, (2019), não detectou melhora significativa com o uso do PRP em relação ao placebo, considerando que a aplicação de PRP neste estudo foi guiada apenas pela palpação do médico. Discussão: Nos estudos deGautam et Al, (2015), Cai et Al, (2019) eKamble et Al, (2022) foi utilizado aplicação guiada por US, demonstrando resultados mais positivos em comparação ao estudo deKeene et Al, (2019), que utilizou a aplicação guiada pela palpação do médico.…”
unclassified
“…Resultados: Neste estudo foram selecionados 4 artigos, os quais 3 apresentaram eficácia significativa na melhora da função e do quadro álgico no membro lesionado após a aplicação de PRP(GAUTAM, et al, 2015; CAI, et al, 2019;KAMBLE, et al, 2022), contudo, o estudo deKeene et al, (2019), não detectou melhora significativa com o uso do PRP em relação ao placebo, considerando que a aplicação de PRP neste estudo foi guiada apenas pela palpação do médico. Discussão: Nos estudos deGautam et Al, (2015), Cai et Al, (2019) eKamble et Al, (2022) foi utilizado aplicação guiada por US, demonstrando resultados mais positivos em comparação ao estudo deKeene et Al, (2019), que utilizou a aplicação guiada pela palpação do médico. Quanto ao método de preparo, a dupla centrifugação demonstrada nos estudos de Cai et Al, (2019) eKamble et Al, (2022), também foi associada a maiores benefícios em comparação a uma única centrifugação do estudode Keene et Al, (2019).…”
unclassified
See 1 more Smart Citation